Natural outcrossing and isolation distance requirements in exserted stigma tomato (Solanum lycopersicum) seed production - PADMINI, K; SADASHIVA, A T; NAIK, L B (The Indian Journal of Agricultural Sciences, 2014)
Genetic purity is of utmost important in seed production of varieties and hybrids. Since exserted stigma tomato types are much prone to natural crossing the chances of genetic contamination is higher in seed production and the recommended isolation requirements for hybrid seed production is higher (200m for foundation seeds and 100m for certified seeds). Hence, studies were conducted at Indian Institute of Horticultural Research, Bangalore, during rabi season of three years, 2007 to 2010 with an objective of determining the extent of natural cross pollination in terms of genetic contamination and to optimize the minimum isolation distance requirements for maintaining genetic purity in seed production of exserted stigma (recessive) tomato. The natural out crossing, i.e. genetic contamination was within 2% (permissible genetic standards) at a minimum isolation of 50m in interior rows of seed plots (R2 and R3) and in all the three years of study. Hence, a safer minimum isolation of 50 m with border rows is sufficient for tomato seed production using exserted stigma Ex-3 as seed parent for obtaining seeds of permissible genetic purity standards (98 %) under IIHR, Bangalore conditions, which is lesser than the recommended isolation of 200m for foundation seeds and 100m for certified seeds in hybrid seed production of tomato.